Climate biocapacity of Mongolia and its change - L, Natsagdorj; B, Munkhbat; P, Gomboluudev (Proceedings of the Mongolian Academy of Sciences, 2019)
This paper has looked into the estimated results of climate biocapacity in Mongolia. The soil moisture supply was assessed through annual precipitation, Shashko’s humidity coefficient, Selyainov’s heat-moisture coefficient and Ivanov-Mezentsev climate biological productivity index. Finally, their long-term trends have been considered as well. The results are consistent with vegetation zones, summer mean pasture yield and existing arable farming region in the country. Therefore, the results are applicable in Mongolia’s conditions. Also, the heat supply during growing season is estimated by daily average temperature, which fluctuates from 5 and 10oC in spring and autumn respectively, the sum total of effective and active temperature. Since 1960, the growing season in the country has lengthened by 3 weeks and the sum of active temperature above 10oC has increased by 80-90oC, although the moisture supply of vegetation is weakening and moreover, climate biocapacity is decreasing.